Assessment of soil microbial and enzyme activity in the rhizosphere zone under different land use/cover of a semiarid region, India - Meena, Archana; Rao, K. S. (Ecological processes, 2021)
Background Land use/cover and management practices are widely known to influence soil organic matter (S OM ) quality and quantity. The present study investigated the effect of different land use, i.e . , forests viz . mixed forest cover (MFC), Prosopis juliflora (Sw.) DC-dominated forest cover (PFC), and cultivated sites viz . agriculture field (AF), vegetable field (VF), respectively, on soil parameter, microbial activity, and enzymes involved in soil nutrient cycle in a semiarid region of India. Results The results showed a significant reduction ( P < 0.05) in soil carbon (S C ), soil nitrogen (S N ) content (~ 30–80%) and consequently the soil microbial biomass carbon (S MBC ) (~ 70–80%), soil basal respiration (S BR ), soil substrate-induced respiration (S SIR ), and soil enzyme activities (β-glucosidase, acid phosphatase, and dehydrogenase) under cultivated sites in comparison with forest sites. Pearson’s correlation showed that a positive correlation of S C with S MBC , S BR , S SIR ( P < 0.01), and enzymatic activities (i.e., β-glucosidase, dehydrogenase) ( P < 0.05) may imply the critical role of S C in regulating microbial and enzymatic activity. Also, a positive correlation of soil moisture with urease activity ( P < 0.01) was found suggesting it as a significant abiotic factor for soil biological functions. Additionally, based on the PCA analysis, we observed the clustering of S MBC /S C ratio and qCO 2 nearby AF. Conclusion Our study suggests that soil microbial parameters (S MBC , S BR , S SIR , S MBC /S C , qCO 2 ) and enzyme activity are key indicators of soil health and fertility. Land use/cover alters the S OM content and soil microbial functions. The management strategies focusing on the conservation of natural forest and minimizing the land disturbances will be effective in preventing soil carbon flux as CO 2 and maintaining the S C stock.